Examining utilization of kidneys as a function of procurement performance. Issue 6 (22nd February 2022) - Doby, Brianna L.; Ross‐Driscoll, Katie; Yu, Sharon; Godwin, Miriam; Lee, Kevin J.; Lynch, Raymond J.
Abstract : Questions have arisen around new metrics for organ procurement organizations (OPO) due to the perception that low‐performing OPOs may be limited by local centers' acceptance of marginal organs. We reviewed 2013–2019 Organ Procurement and Transplantation Network (OTPN) and National Centers for Health Statistics (NCHS) data to explore the relationship between objectively measured OPO performance and utilization of deceased donor kidneys. We found that although donor recovery declined with rising age and kidney donor profile index (KDPI), OPO performance differences were evident within each age/KDPI group. By contrast, the number of discards per donor did not vary with OPO performance. Centers in donor service areas (DSAs) with lower‐performing OPOs had higher local utilization and greater import of high‐KDPI kidneys than did those with higher‐performing OPOs. Lower rates of donor availability relative to waitlist additions may contribute to observed center acceptance behavior. Differences in center‐level performance were highly visible in Scientific Registry of Transplant Recipients (SRTR) organ acceptance metrics, while SRTR OPO metrics did not detect large or persistent variation in procurement performance. Cumulatively, our findings suggest that objective measures of procurement performance can inform discussions of organ utilization, allowing for alignment of metrics in all elements of the procurement‐transplantation system. Abstract : Kidney transplant centers in areas with low organ procurement rates display more aggressive utilization and import of deceased donor kidneys.